Strengthening Banking Security: Pioneering AI-Driven Identity and Access Management Solutions - Avinash Chowdary Vikram (International Journal of Intelligent Systems and Applications in Engineering, 2025)
The banking industry is currently grappling with complex challenges in Identity and Access Management (IAM), which are essential for safeguarding sensitive customer information and maintaining regulatory compliance. As financial institutions evolve and adapt to an increasingly digital landscape, robust security measures are more crucial than ever to protect against a rising tide of sophisticated cyber threats. Traditional IAM approaches often fall short in addressing these evolving threats, as they may lack the agility and intelligence needed to respond effectively. This underscores the urgent need for AI-driven solutions that not only enhance security but also improve operational efficiency.This study delves into the transformative role of Artificial Intelligence (AI) in revolutionizing IAM within the banking sector. By focusing on critical components such as AI-driven authentication, fraud prevention, and risk-based access control, the study illustrates how innovative technologies can mitigate risks while ensuring compliance with regulatory frameworks. For instance, AI enhances authentication processes by utilizing advanced algorithms that analyze user behavior and patterns, making it significantly more difficult for unauthorized users to gain access.The paper includes real-world case studies that demonstrate the effectiveness of AI-based IAM solutions in enhancing security protocols, providing insights into successful implementations that have resulted in reduced instances of fraud and improved customer trust. Additionally, these case studies showcase how financial organizations have leveraged AI to create a more streamlined access control system, allowing users to navigate financial services seamlessly while maintaining a stringent security posture.